Penguatan Kapasitas Digital UMKM Desa Menganti melalui Pelatihan Pemanfaatan Aplikasi Online untuk Pemasaran Produk - LINDA PERDANA WANTI; Rahmawan Bagus Trianto; Abdul Rohman Supriyono; Annisa Romadloni; Muhammad Abdul Muin; Antonius Agung Hartono; Hety Dwi Hastuti (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Menganti Village, Cilacap Regency, play a vital role in driving the local economy, yet they face limitations in utilizing digital technology for product marketing. Most MSMEs still rely on conventional marketing methods, resulting in relatively limited market reach and competitiveness. This community service program aims to improve the digital capacity of MSMEs through training in the use of online applications as a means of marketing their products. The program implementation method includes needs identification, outreach, hands-on training, and mentoring in the use of digital marketing applications, such as social media and marketplace platforms. The training focused on digital account management, creating simple promotional content, and implementing easy-to-implement online marketing strategies tailored to the characteristics of village MSME products. The results of the program indicate an increase in the knowledge, skills, and confidence of MSMEs in utilizing online applications to market their products more widely. Participants are now able to manage digital media independently and understand the importance of digital marketing as part of business development. This program is expected to encourage the independence and sustainability of MSMEs in Menganti Village in facing the challenges of the digital economy and continuously increase the competitiveness of local products.